Pengaruh Emotional Freedom Technique Untuk Mengatasi Kecemasan Mahasiswa Jurusan Fisioterapi Dalam Menghadapi Ujian Akhir Semester - Muhammad Mudatsir Syatibi; Noerdjanah (Nur Science Institute, 2022)
The aims of this research is to determine the effect of Spiritual Emotional Freedom Technique (SEFT) on overcoming anxiety of students in Physiotherapy Department in facing final semester exams. This research use One group pre and posttest design with Control with the subjects is D-III Physiotherapy studi program students in the second semester of the 2021-2022 academic year who meet the inclusion and exclusion criteria. The number of subjects as many as 72 people. The subject of group I (treatment group) was given treatment in the form of giving SEFT which was carried of by the subject themselves 6 times in 6 days (one time perday). Research location on the campus of the Department of Physiotherapy, Poltekkes Surakarta Implementation time from April to June 2022. Research measuring instrument use Hamilton Anxiety Rating Scale (HARS). Normality test using the Kolmogorov-Smirnov test and homogenity test using Levene’s test. The difference test between before and after treatment used the Wilcoxon test and the difference test between group I and group II after treatment used the Mann Whitney test. The conclusion of this research is SEFT can overcome the anxiety of students majoring in physiotherapy at Poltekkes Surakarta in facing the end of semester exams.